Interaction at the silicon/transition metal oxide heterojunction interface and its effect on the photovoltaic performance. Issue 41 (30th September 2015) - Liang, Zhimin; Su, Mingze; Zhou, Yangyang; Gong, Li; Zhao, Chuanxi; Chen, Keqiu; Xie, Fangyan; Zhang, Weihong; Chen, Jian; Liu, Pengyi; Xie, Weiguang
Abstract : The interfacial reaction and energy level alignment at the Si/transition metal oxide (TMO, including MoO3− x, V2 O5− x, WO3− x ) heterojunction are systematically investigated. Abstract : The interfacial reaction and energy level alignment at the Si/transition metal oxide (TMO, including MoO3− x, V2 O5− x, WO3− x ) heterojunction are systematically investigated. We confirm that the interfacial reaction appears during the thermal deposition of TMO, with the reaction extent increasing from MoO3− x, to V2 O5− x, and to WO3− x . The reaction causes the surface oxidation of silicon for faster electron/hole recombination, and the reduction of TMO for effective hole collection. The photovoltaic performance of the Si/TMO heterojunction devices is affected by the interface reaction. MoO3− x are the best hole selecting materials that induce least surface oxidation but strongest reduction. Compared with H-passivation, methyl group passivation is an effective way to reduce the interface reaction and improve the interfacial energy level alignment for better electron and hole collection.